Designing constructionist futures : the art, theory, and practice of learning designs - Holbert, Nathan; Berland, Matthew; Kafai, Yasmin B. (The MIT Press, 2020)
A diverse group of scholars redefine constructionism introduced by Seymour Papert in 1980 in light of new technologies and theories. Constructionism, first introduced by Seymour Papert in 1980, is a framework for learning to understand something by making an artifact for and with other people. A core goal of constructionists is to respect learners as creators, to enable them to engage in making meaning for themselves through construction, and to do this by democratizing access to the world's most creative and powerful tools. In this volume, an international and diverse group of scholars examine, reconstruct, and evolve the constructionist paradigm in light of new technologies and theories. Taken together, their contributions show that constructionism has advanced in educational research and practice and also that, in turn, researchers and practitioners can learn from constructionism how to foster learning in ways that respect learners' creativity and communities. The contributors examine how constructionist design can function within contexts ranging from school and home to virtual spaces; explore ways to support learners who have been under-resourced, overlooked, or oppressed; discuss learning by collaboration; and consider the implications of learning as a creative process of construction, exploring ways to support creative enterprises within the constraints of formal classrooms. Finally, leading visionaries imagine where constructionism, design, and research will go next. - Resumé vydavatel
Keywords: konstruktivistická pedagogika; počítačová věda; studium a výuka; constructivist education; computer science; study and teaching; elektronické knihy; sborníky; electronic books; papers of several authors